TEACHER’S USE OF TRANSLATION AS INSTRUCTIONAL STRATEGY IN TEACHING ENGLISH - Kartinisari K.R.; Batan I Gede; Adnyani L.D.S. (Universitas Pendidikan Ganesha, 2018)
The teacher often uses translation or mother tongue (L1) during the instructional process in EFL classroom. However, the use of translation is still going debated. In order to make the best use of translation in instructional process, it is necessary to know when and why the teacher uses it. Related to this present study, there were two aims of the study, namely to find out in what situations do the teacher use translation and to find out the teachers’ reasons for using translation in relating to the situation of classroom instructional process. This study followed qualitative interactive descriptive approach. There were three English teachers at the 7th grade classes at SMP Negeri 4 and SMP Negeri 5 Singaraja as the subjects of the study. The data was collected through observations and interviews. The data obtained were analyzed descriptively. The results of study showed that the teachers used translation (L1) in such situation, namely: (i) giving instruction, (ii) presentation, (iii) checking comprehension, (iv) language testing/language assessment, and (v) eliciting language. In addition, there were two reasons of using translation by the teachers namely, the students did not understand many vocabularies, sentences, and material given in English and the students felt uncomfortable if the teacher used English only in the classroom.